Implementasi Manajemen Pembelajaran Karakter Berbasis Total Quality Management Di SMP Muhammadiyah 3 Yogyakarta - Yoga Anjas Pratama (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2019)
Character learning based on Total Quality Management is the process, transfer, habituation, and formation of character values by educators to students, which are carried out based on the total quality management concept, namely: quality, customer satisfaction, continuous improvement, and overall in all organizational components. This research is qualitative descriptive field research which is background by the high level of juvenile delinquency or moral deviation as a result of the lack of cultivation of character values in students. Therefore, in this study, the author took the location of research at Muhammadiyah 3 Middle School in Yogyakarta, who apply total quality management based character learning. From the research carried out found things, as follows: (1) Muhammadiyah 3 Middle School Yogyakarta has instilled and applied character values (religious, nationalist, independent, and mutual cooperation) through school activities (2) Muhammadiyah 3 Middle School Yogyakarta has implemented the concept of Total Quality Management in character learning (3) Muhammadiyah Middle School 3 Yogyakarta has implemented the 2013 curriculum in the character learning process based on Total Quality Management, which is adjusted to the learning steps, although basically there are still many who need continuous improvement efforts.